Uncovering Factors Affecting Employee Performance in the Poultry Processing Industry in Kuningan Regency: Competency, Training, and Compensation - Syahdu Fatham Mubina; Anggara Anggara; Lisa Harry Sulistiyowati; Sunimah Sunimah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Enhancing employee performance is influenced by competence, training, and pay. The study’s goal was to examine how these three elements affected worker performance in Kuningan’s poultry processing sector. The study employed a quantitative, associative research design. Out of 242 employees, 151 respondents were chosen for the study using a purposive sampling technique. Using SmartPLS software, questionnaires with a five-level Likert scale were distributed in order to collect data, which was then analyzed using the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS). The findings indicated that while compensation did not significantly affect employee performance on its own, competency and training did. On the other hand, with a 54.1% contribution, competence, training, and pay all significantly affect employee performance. Competency is the variable that influences other variables the most strongly.